Chemistry and Bioactivities of Six Tunisian Eucalyptus Species - Habiba Kouki; Flavio Polito; Laura De Martino; Yassine Mabrouk; Lamia Hamrouni; Ismail Amri; Florinda Fratianni; Vincenzo De Feo; Filomena Nazzaro (MDPI AG, 2022)
The complex taxonomy of Eucalyptus genus, the renewed interest in natural compounds able to combat microbial strains, the overuse of synthetic pesticides, the consequent request for alternative control methods were the reasons for this research. The essential oils (Eos) of Eucalyptus bosistoana, Eucalyptus melliodora, Eucalyptus odorata, Eucalyptus paniculata, Eucalyptus salmonopholia, and Eucalyptus transcontinentalis were analyzed by GC/MS and their potential phytotoxic activity was evaluated against the germination and radicle elongation of Sinapis arvensis, Raphanus sativus and Lolium multiflorum. The antibiofilm activity was assayed against both Gram-positive (Staphylococcus aureus and Listeria monocytogenes) and Gram-negative (Pseudomonas aeruginosa, Escherichia coli, and Acinetobacter baumannii) bacteria. Monoterpenoids were the most representative constituents in all EOs and eucalyptol was the dominant component except in E. melliodora EO, in which p-cymene was the most abundant. In phytotoxic assays, the EOs from E. odorata and E. paniculata were the most active against germination and radical elongation of the tested seeds. Finally, the Eucalyptus EOs proved their capacity to effectively inhibit the adhesion process of all five pathogen strains, with percentages often reaching and exceeding 90%. These Eucalytpus EOs could have possible employments in the food, health and agricultural fields.